Answer:
[tex](g\circ f)(x)=-6x^2 +8x +7[/tex]
Step-by-step explanation:
The Composite Function
Given f(x) and g(x) real functions, the composite function, named (g\circ f)(x) is defined as:
[tex](g\circ f)(x)=g(f(x))[/tex]
For practical purposes, it's found by substituting f into g.
Given the functions:
[tex]f(x) = 3x^2 - 4x - 1[/tex]
[tex]g(x) = -2x + 5[/tex]
We need to find
[tex](g\circ f)(x)=g(f(x))[/tex]
Replace f into g:
[tex](g\circ f)(x)=-2(3x^2 - 4x - 1) + 5[/tex]
Operating:
[tex](g\circ f)(x)=-6x^2 +8x +2 + 5[/tex]
Reducing:
[tex](g\circ f)(x)=-6x^2 +8x +7[/tex]
Thus,
[tex]\boxed{(g\circ f)(x)=-6x^2 +8x +7}[/tex]